The didactic side in the grammatical bookmarks A study beyond poetics systems of Mohammed Ben Oba Elmouzamiri and Mohammed Bai Belaalem - ammari, Abdallah (Milev Journal of Research and Studies, 2019)
Through this study we are planning to keen on the light of the didactic side;which adopted by Mohammed Ben Oba Elmouzamiri and Mohammed Bai Belaalem in their grammatical bookmarks; whereas we give a snapshot arrises the emergence of that side and it's founders; then we presenting the two famous Imams ;as well as tackling a study beyond their grammatical bookmarks; reaching towards that side aspects and how could it contribute in facilitating the Arabic grammar.